2016
DOI: 10.1038/eye.2016.182
|View full text |Cite
|
Sign up to set email alerts
|

Design and performance of a large lumen glaucoma drainage device

Abstract: Purpose We report the in vivo testing of a large-lumen glaucoma drainage (LL-GDD) device equipped with a flow regulator. The device's membrane can be non-invasively opened with laser in the postoperative period to adjust aqueous flow and intraocular pressure. Methods The initial LL-GDD prototypes were constructed using 22 G silicone angiocatheters cut down to size. A 10 nm PVDF membrane was then affixed to the end using cyanoacrylate. The LL-GDD was tested first in a model eye equipped with ports for infusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In contrast, there is a report that the filtration rate declines when the inner diameter of the tubing is reduced in BI [21]. An in vivo study showed that a large-lumen glaucoma drainage device equipped with a flow regulator can provide both prevention of immediate postoperative hypotony and progressive IOP reduction on demand [22]. A similar technique of inserting a double XEN to improve filtration was reported at the 9th World Glaucoma E-Congress [23].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there is a report that the filtration rate declines when the inner diameter of the tubing is reduced in BI [21]. An in vivo study showed that a large-lumen glaucoma drainage device equipped with a flow regulator can provide both prevention of immediate postoperative hypotony and progressive IOP reduction on demand [22]. A similar technique of inserting a double XEN to improve filtration was reported at the 9th World Glaucoma E-Congress [23].…”
Section: Discussionmentioning
confidence: 99%
“…A series of newly designed GDDs can be adjusted post-operatively to reduce the incidences of hypotony and hypertension. These devices include the eyeWatch (eW, Rheon Medical, Lausanne, Switzerland) and others currently undergoing animal testing [ 57 , 58 ]. The eW has a deformable silicone tube that can undergo targeted compression to alter its cross-sectional area and thereby change fluidic resistance.…”
Section: Glaucoma Drainage Devicesmentioning
confidence: 99%